Secure And Effective Image Authentication And Copyright Protection Using Integer Wavelet Transform - Ng, Ching Onn (2023)
Widespread usage of the internet and digital communication technologies, multimedia data may be vulnerable to piracy as unauthorized users can easily alter multimedia data such as image. To increase the robustness and security of images, a dual watermarking system were introduced by combining multiple watermarks into a single content. The use of multiple watermarks enhances the ability to detect and identify the copyright owner in the case of unauthorized use or any altering on the content. In this study, IWT and SVD based on human visual characteristics are proposed, to embed the watermark in the image, making it more resistant to attacks while lower the distortion on image quality. The method helps to ensure that RGB supported digital images are protected by copyright and can be authenticated if there is any tampering. Various geometrical, compression, and image processing attacks are used to test the effectiveness of the proposed approach. Hence, the test results are compared to other dual watermarking systems.